The social dynamics of collaboration, trust and recognition in the heart of food and agricultural equipments design process in West Africa : the case of Burkina Faso - (:unkn) unknown (My University, 2011)
Within the handicraft and the semi-industrial environment, technical artifacts design in West African developing countries and particularly in Burkina Faso is a major challenge. However, the vast majority of technologies transferred have not met the target populations' expectations. For many failures mark the recent history of these attempts. This technological impasse is more often raised by designers and developers in terms of developing a specific design method for these developing countries. This thesis draws attention to the fact that technical artifacts design in this region cannot be done without a critical reflection on the design process implementation modalities. It is no longer only assisting the technical systems design by developing a suitable design method, but going beyond, as possible as, to extend the knowledge scope and to analyze all of the actors linked to the socio-technical networks involved, in order finally, to help designing a new technical system taking into account, as soon as the upstream, issues such as collaboration conditions, trust building and designers' acknowledgment and recognition.
Keywords: African Research